Bulk heterojunction thickness uniformity – a limiting factor in large area organic solar cells?. Issue 10 (1st July 2015) - Jin, Hui; Armin, Ardalan; Hambsch, Mike; Lin, Qianqian; Burn, Paul L.; Meredith, Paul
<x xml:space="preserve">Abstract</x> It is commonly thought that inhomogeneities in the bulk heterojunction thickness of donor:acceptor organic solar cells are a major efficiency‐limiting factor in scaling to modules. This is primarily related to degradation of the charge collection efficiency associated with the thicker segments of the active layer and/or loss of fill factor from thin segments where shorting occurs. We study the former effect in two model polymer–fullerene organic solar cell blend systems with very different charge transport properties: poly(3‐n‐hexylthiophene):[6, 6]‐phenyl‐C61‐butyric acid methyl ester (P3HT:PC60BM) and poly[N‐9"‐heptadecanyl‐2, 7‐carbazole‐alt‐5, 5‐(4′, 7′‐di‐2‐thienyl‐2′, 1′, 3′‐benzothiadiazole)]:[6, 6]‐phenyl‐C71‐butyric acid methyl ester (PCDTBT:PC70BM). We find that junction thickness inhomogeneities do not cause substantial power losses in large area cells (5 × 5 cm2 monolithic submodules) when the bimolecular recombination dynamics are suppressed, i.e., the system is non‐Langevin. This insight into the scaling physics of organic solar cells suggests that non‐Langevin materials will deliver more robust and viable large area manufacturing opportunities.